The Effect of Education on Knowledge of Sexually Transmitted Infections in Women of Reproductive Age at Lee Health Center, North Morowali Regency - Mutmaina; Sakulat, Gabriella (Literasi Indonesia Emas (PT), 2025)
Introduction: Women's health, both in youth and adulthood, often faces reproductive health issues such as infections of the reproductive organs, including sexually transmitted infections (STIs). Education on STIs is essential for improving awareness and prevention. Objective: The aim of this study was to provide education about STIs to women of reproductive age and assess the improvement in their knowledge. Method: This is a quantitative study with a quasi-experimental design using a one-group pretest and posttest approach. The sample consisted of 30 women of reproductive age, selected through total sampling. Data were collected using a questionnaire, and data analysis was performed using the Wilcoxon statistical test with a significance level of α = 0.05. Results: After receiving education on STIs, 19 respondents (63.3%) demonstrated good knowledge, 11 respondents (36.7%) had sufficient knowledge, and no respondents had poor knowledge. The analysis revealed a significance value of Sig < 0.05, indicating a significant effect of the education on improving knowledge about STIs in women of reproductive age. Conclusion: The study concluded that education significantly improved the knowledge of women of reproductive age about sexually transmitted infections, highlighting the importance of such educational interventions in promoting better reproductive health awareness.